Role of Communication Strategies in Organizational Commitment, Mediating Role of Faculty Engagement: Evidence From English Language Teachers - Ma, Yan (Frontiers in Psychology, 2022)
Employees are critical stakeholders for the organization because they directly deal with the end-users and represent the entire firm. To recognize the strategic importance of the employees, organizations create communication programs to keep employees apprised of organizational issues. In this regard, the present study examined the role of communication strategies (i.e., information flow, information adequacy, and information feedback) on organizational commitment. The study also investigated the mediating effect of faculty engagement between communication strategies and organizational commitment. Self-administered survey aided in acquiring data from 276 English language teachers in China. The analysis of the data was conducted using SmartPLS through the SEM technique. The outcome of the study demonstrated that information flow and information feedback significantly impact organizational commitment and faculty engagement. The analysis also revealed that information adequacy significantly impacts organizational commitment but has no relationship with faculty engagement. The mediation analysis demonstrated that faculty engagement mediated the relationship between information flow and organizational commitment and between information feedback and organization commitment. However, faculty engagement did not mediate the relationship between information adequacy and organizational commitment among English language teachers in China. In theoretical terms, the study contributed in terms of incorporating different communication strategies and examining their effect on organizational commitment and faculty engagement. In practical terms, the present study would be beneficial for the management of the educational institutes to develop different ways of enhancing communication strategies within the institute. This paper also provided directions for the future, for example, conducting the study on other subject teachers, increasing the sample, carrying out the research in a different context, and adding different mediators and moderators in the existing model.